The development of recovery based nursing in a high-security hospital: nurturance and safe spaces in a dangerous world?. Issue 4 (4th November 2014) - Chandley, Mark; Cromar-Hayes, Maxine; Mercer, Dave; Clancy, Bridget; Wilkie, Iain; Thorpe, Gary
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to derive from an on-going, innovative, project to explore the concept, and application, of "recovery" in the care and clinical management of patients detained in one UK high-security hospital. Design/methodology/approach – Utilising a qualitative, action research, methodology the aim was to involve forensic mental health nurses in a collaborative, client-centred approach to identification and resolution of dilemmas in the process of planning care for offender-patients. Findings – In this context the authors identify constraints and contradictions involved in employing recovery principles in institutions critics refer to as part of the disciplinary apparatus of psychiatric and social control; where the taken for granted lives, and relations, of an incarcerated population are measured by the calendar, not the clock. Research limitations/implications – Protective practices remain highly relevant in high-secure practice. Safety, an important value for all can by and large be achieved through recovery approaches. The humanistic elements of recovery can offer up safe and useful methods of deploying the mental health nurse on the ward. Many nurses have the prerequisite approach but there remains a wide scope to enhance those skills. Many see the approach as axiomatic though nurse education often prepares nurses with a biomedical view of the ward. Practical implications – Currently, philosophical tenets of recovery are enshrined in contemporary health policy and professional directives but, as yet, have not been translated into high-secure settings. Drawing on preliminary findings, attention is given to the value of socially situated approaches in challenging historic dominance of a medical model. Social implications – It is concluded that recovery could be a forerunner of reforms necessary for the continued relevance of high-secure care into the twenty-first century. Originality/value – This research is located in high-secure setting. The social situation is marked by the extent of the isolation involved. A value is in this situation. First it is akin to the isolation of the tribe utilised by many anthropologists for their ability to adopt the "social laboratory" status to test out theories of behaviour in industrial society. The authors urge others to utilise this research in this way. Second, the situation represents the locus of so many of societies dilemmas, paradoxes and fears that moral issues morph from what is the mundane in wider society. In this way humanistic approaches are tested via action research with nurses in some rigouous ways.